Odpowiedź :
Równanie I:
[tex]5x + 4 = 10 \ \ \ \ \ \ \ \ \ \ \ \ \ \ /-4\\5x = 6 \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ / :5\\\boxed{x = 1,2}[/tex]
Równanie II:
[tex]3x - 5 = 9 \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ /+5\\3x = 14 \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ /:3\\\boxed{x = 4\frac{2}{3}}[/tex]
Równanie III:
[tex]-2x + 3 = 7 \ \ \ \ \ \ \ \ \ \ \ \ \ /-3\\-2x = 4 \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ /:(-2)\\\boxed{x = -2}[/tex]
Równanie IV:
[tex]-4x-3=13 \ \ \ \ \ \ \ \ \ \ \ \ \ /+3\\-4x = 16 \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ /:(-4)\\\boxed{x = -4}[/tex]
5x + 4 = 10 / -4
5x = 6 / :5
x = 6/5
3x - 5 = 9 / +5
3x = 14 / :3
x = 4 2/3
-2x + 3 = 7 / -3
-2x = 4 / :(-2)
x = -2
-4x - 3 = 13 / +3
-4x = 16 / :(-4)
x = -4
5x = 6 / :5
x = 6/5
3x - 5 = 9 / +5
3x = 14 / :3
x = 4 2/3
-2x + 3 = 7 / -3
-2x = 4 / :(-2)
x = -2
-4x - 3 = 13 / +3
-4x = 16 / :(-4)
x = -4